2006
DOI: 10.1093/ps/85.10.1722
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circulating Levels of Serotonin and Immunological Changes in Laying Hens Divergently Selected for Feather Pecking Behavior

Abstract: The aim of this study was to investigate the changes in immunological parameters as well as changes with respect to plasma levels of serotonin and tryptophan in lines selected for and against feather pecking (FP) behavior [high FP (HP) line and low FP (LP) line] for 5 generations. The hens from the HP line had a higher plasma serotonin level than those from the LP line (0.059 vs. 0.037 micromol/L, F(2,27) = 0.031, P < 0.05). The plasma level of tryptophan was, on average, 67.30 micromol/L and did not differ be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 19 publications
10
36
3
Order By: Relevance
“…Combining their results with the ones of the present study, we see that in the case of HTR2C higher feather damage corresponds to lower complement activity. Buitenhuis et al (2006) found higher IgG titres and lower leukocyte concentration, CD4? lymphocytes percentage and MHC I expression in high FP compared to low FP lines.…”
Section: Methodsmentioning
confidence: 89%
“…Combining their results with the ones of the present study, we see that in the case of HTR2C higher feather damage corresponds to lower complement activity. Buitenhuis et al (2006) found higher IgG titres and lower leukocyte concentration, CD4? lymphocytes percentage and MHC I expression in high FP compared to low FP lines.…”
Section: Methodsmentioning
confidence: 89%
“…Like dopamine, this system is known to influence locomotor and exploration behaviour in rodents (Buhot and Naili 1995). Manipulations of the serotonin system have also been found to affect feather pecking behaviour in laying hens van Hierden et al 2004) and serotonin levels in plasma seems to be higher in the HFP line compared to the LFP line (Buitenhuis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Total number of white blood cells increased in the LP line compared to the control line (Buitenhuis et al, 2006). Whether the cause of this increase is due to a specific sub type of leukocyte can not be detected, but the result of Cheng et al (2001b) suggest that there is a shift in the amount of heterophils and lymphocytes in the line selected for reduced mortality.…”
Section: Comparison Of the Studiesmentioning
confidence: 89%
“…In 1995, 15 sires and 60 dams were randomly picked from the White Leghorn layer line to generate the base population (generation 0). In the fifth generation of selection different production traits, immunological parameters and plasma serotonin concentrations were measured (Buitenhuis et al, 2006;Su et al, 2006). A random bred control line was maintained from the base population.…”
Section: Description Of the Danish Selection Experimentsmentioning
confidence: 99%
See 1 more Smart Citation